2022
DOI: 10.1002/ijc.34300
|View full text |Cite
|
Sign up to set email alerts
|

Exposures to pesticides and risk of cancer: Evaluation of recent epidemiological evidence in humans and paths forward

Abstract: Knowledge of the role in cancer etiology of environmental exposures as pesticides is a prerequisite for primary prevention. We review 63 epidemiological studies on exposure to pesticides and cancer risk in humans published from 2017 to 2021, with emphasis on new findings, methodological approaches, and gaps in the existing literature. While much of the recent evidence suggests causal relationships between pesticide exposure and cancer, the strongest evidence exists for acute myeloid leukemia (AML) and colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 171 publications
(651 reference statements)
1
7
0
Order By: Relevance
“…Overall – although not many – studies were of high quality and suggested a role of pesticide exposure through food on health, in particular, risk of cancer and subsequent mortality. This seems consistent with a recent systematic review on pesticides and risk of cancer [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…Overall – although not many – studies were of high quality and suggested a role of pesticide exposure through food on health, in particular, risk of cancer and subsequent mortality. This seems consistent with a recent systematic review on pesticides and risk of cancer [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
“…Direct contact with pesticides is the leading cause of cancer around the world. This is a global issue that is presently fascinating researchers from all around the world [ 185 , 186 ].…”
Section: Resultsmentioning
confidence: 99%
“…The NAFLD studies found a positive association with cancer and exposure to heavy metals, methyl tertiary-butyl ether and selenium and no association with trihalomethanes [31]. Even though recent evidence suggests causal relationships between PE and cancer, the most robust evidence exists for acute myeloid leukaemia (AML) and colorectal cancer (CRC) [32].…”
Section: Environmental Exposures Including Pesticides and Liver Cancermentioning
confidence: 99%